2002
DOI: 10.4049/jimmunol.169.11.6459
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Membrane IL-5 Receptor α on Human Eosinophils: II. IL-5 Down-Modulates Its Receptor Via a Proteinase-Mediated Process

Abstract: In the accompanying study, we demonstrated that following Ag challenge, membrane (m)IL-5Rα expression is attenuated on bronchoalveolar lavage eosinophils, soluble (s)IL-5Rα is detectable in BAL fluid in the absence of increased steady state levels of sIL-5Rα mRNA, and BAL eosinophils become refractory to IL-5 for ex vivo degranulation. We hypothesized that IL-5 regulates its receptor through proteolytic release of mIL-5Rα, which in turn contributes to the presence of sIL-5Rα. Purified human peripheral blood eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 40 publications
7
107
0
1
Order By: Relevance
“…Studies by Bates et al (38) using eosinophils obtained from bronchoalveolar lavage fluid documented a decreased responsiveness of cells to IL-5 stimulation that was paralleled by a decreased expression of the ␣-chain of the IL-5 receptor. These findings were independently confirmed by Liu et al (36,37) who reported distinct regulation of the receptors for IL-3, GM-CSF, and IL-5. In vitro studies showed that 24 h of stimulation of eosinophils with IL-5 resulted in the down-regulation of expression of the ␣-chains of the receptors for IL-5 and GM-CSF and in up-regulation of the ␣-chain of the IL-3 receptor (30).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Studies by Bates et al (38) using eosinophils obtained from bronchoalveolar lavage fluid documented a decreased responsiveness of cells to IL-5 stimulation that was paralleled by a decreased expression of the ␣-chain of the IL-5 receptor. These findings were independently confirmed by Liu et al (36,37) who reported distinct regulation of the receptors for IL-3, GM-CSF, and IL-5. In vitro studies showed that 24 h of stimulation of eosinophils with IL-5 resulted in the down-regulation of expression of the ␣-chains of the receptors for IL-5 and GM-CSF and in up-regulation of the ␣-chain of the IL-3 receptor (30).…”
Section: Discussionsupporting
confidence: 61%
“…7A). Because reports of down-regulation of high-affinity receptors (␣-chains) and proteolytic degradation of ␤-chain GM-CSF/IL-5/IL-3 receptor (30,36,37) suggested relative independence of GM-CSFinduced eosinophil activation with constant GM-CSF stimulation, we tested the effect of GM-CSF inhibition on eosinophil survival and compared it with the effect of ICAM-1 blockade. First, we added GM-CSF-neutralizing Ab before and 3 h after GM-CSF stimulation.…”
Section: Blockade Of Icam-1 Expression Inhibits Prolongation Of Eosinmentioning
confidence: 99%
“…Recently, it has been demonstrated that IL-5 can down-modulate its receptor, thereby limiting IL-5-dependent inflammatory conditions. Moreover, this down-modulation could be partially reversed through MMP inhibitors, BB-94 and GM6001, suggesting contribution from an MMPdependent pathway (28).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the levels of IL-5 in the epithelial lining fluid of these subjects (all of whom were dual responders) are estimated to be ϳ10 -100 ng/ml. Treatment of blood eosinophils in vitro with IL-5 at concentrations in this range is known to saturate the IL-5 receptor (63-68) and lead to ␣ M ␤ 2 up-regulation and activation and induction of adhesion to ICAM-1 and other substrates (36,60,61), priming and enhanced response to chemoattractants (69), enhanced viability (70), degranulation and granule protein release (30), IL-5 receptor ␣ down-regulation (71), and enhanced expression of certain genes (72). In contrast, median concentrations of the other IL-5 family cytokines before dilution are estimated to be ϳ1-3 ng/ml.…”
Section: Discussionmentioning
confidence: 99%